Optical Fiber Spool Acoustic Wave Resonances Employing a Mach-Zehnder Interferometer in Vacuum Chamber - Rodigheri,Mareli (2020)
Abstract The longitudinal, flexural, and torsional modes of acoustical resonances are presented for a long and small thickness cylindrical fiber spool. The fiber spool is built using a monomode optical fiber tightly wound in a helix form around a cylindrical Styropor. The acoustical resonance values are obtained using a Mach Zehnder interferometer with the fiber spool in the long (2 km) arm and a small linewidth laser. To reduce spurious signals, the interferometer was placed inside a vacuum chamber. The measured and theoretical results reasonably agree up to the first fifteen resonant longitudinal modes and for the first five flexural and torsional resonant modes, with a span from 10 Hz up to 200 Hz.